Epicardial Fat in Atrial Fibrillation and Heart Failure - Iacobellis, G.; Zaki, M. C.; Garcia, D.; Willens, H. J. (Hormone and Metabolic Research, 2014)
Obesity is a well-known risk factor for atrial fibrillation (AF) and heart failure (HF). Epicardial fat, the true visceral fat depot of the heart, has been associated with changes in both cardiac function and morphology. In this study, we evaluated whether ultrasound-measured epicardial fat thickness is related to AF and HF. A cross-sectional study was performed in 84 consecutive subjects with clinical and ECG-documented history of permanent (AF) or paroxysmal AF (PAF) who underwent echocardiographic epicardial fat thickness measurement. Sixty-four subjects had AF and 20 showed PAF. AF subjects had higher prevalence of heart failure (HF), defined by ejection fraction (EF)<50%, (p<0.01). Subjects with AF had higher epicardial fat thickness than PAF subjects (4.8±2.5 vs. 3.5±2.4 mm, p<0.05). As subjects were stratified by HF, epicardial fat thickness was lower (4.4±2.2 vs. 5.4±2.3 mm, p<0.05) in those with HF as compared to subjects without HF. This study showed for the first time that echocardiographic epicardial fat thickness is significantly higher in subjects with chronic AF when compared to those with PAF. It is plausible that permanent AF is related to long-term influence of epicardial fat. Epicardial fat reduction in HF subjects may reflect the overall fat mass reduction, commonly observed in these patients. It is also possible to hypothesize that epicardial fat pad may incur in fibrotic changes during chronic cardiac failure.
Keywords: epicardial fat; atrial fibrillation; heart failure; echocardiography; obesity